A numerical study of the influence of interface morphology on the stress behavior in thermal barrier coatings near an inclined film-cooling hole. Issue 11 (1st August 2020) - Cai, Zhenwei; Hong, Hui; Peng, Di; Zhao, Xiaofeng; Wang, Weizhe; Liu, Yingzheng; Cao, Zhaomin
Abstract: Early failure induced by the cooling-hole structure and the interface morphology has significant influence on the integrity of thermal barrier coatings (TBCs). Thus, understanding the influence of interface morphology in TBCs on the stress behavior near an inclined film-cooling hole is highly desirable for evaluating the reliability of TBCs. In this study, a two-dimensional (2D) submodel of TBCs around a cooling hole was established to numerically investigate the influence of interface morphology in TBCs on the stress behavior near an inclined film-cooling hole. The results showed that the rough interface aggravated the stress state at both the top coat/thermally grown oxide (TC/TGO) and bond coat/thermally grown oxide (BC/TGO) interfaces. The maximum tensile stress appeared at the cooling-hole edge in the TC, whereas the maximum tensile stress occurred at the peaks of the BC. The different starting locations of the interface morphology from the cooling-hole edge had a significant effect on the stress behavior near the cooling-hole edge in TC, but they had no influence on the stress behavior in the BC. With increasing amplitude, the maximum tensile stress in the TC initially increased and then decreased. The interface asperity may have accelerated crack initiation at the peaks of the BC, but it had no influence on the stress level of the zone near the cooling-hole edge.